Sulfur dioxide residue in sulfur-fumigated edible herbs: The fewer, the safer?. (1st February 2016) - Duan, Su-Min; Xu, Jun; Bai, Ying-Jia; Ding, Yan; Kong, Ming; Liu, Huan-Huan; Li, Xiu-Yang; Zhang, Qing-Shan; Chen, Hu-Biao; Liu, Li-Fang; Li, Song-Lin
Highlights: SO2 for indicating safety of sulfur-fumigated edible herbs was challenged. Residual SO2 content was dynamically determined in ASR during sulfur-fumigation. Ten major bioactive chemicals in ASR were quantitatively analyzed meanwhile. Relationship between their content variation tendency was discussed. SO2 alone might be unable to evaluate safety of sulfur-fumigated edible herbs. Abstract: The residual content of sulfur dioxide is frequently regarded as the exclusive indicator in the safety evaluation of sulfur-fumigated edible herbs. To examine the feasibility of such assessment criteria, here the variations in residual sulfur dioxide content during sulfur-fumigation and the potential mechanisms involved were investigated, using Angelicae Sinensis Radix (ASR) as a model herb. The residual sulfur dioxide content and ten major bioactive components in sulfur-fumigated ASR samples were dynamically examined at 13 successive time points within 72 h sulfur-fumigation. The relationship between the content variation tendency of sulfur dioxide and the ten chemicals was discussed. The results suggested that sulfur dioxide-involved chemical transformation of the original components in ASR might cause large consumption of residual sulfur dioxide during sulfur-fumigation. It implies that without considering the induced chemical transformation of bioactive components, the residual sulfur dioxide content alone might be inadequate to comprehensively evaluate the safety of sulfur-fumigated herbs.